Getting started in mutual funds - Hall, Alvin D. (John Wiley & Sons, 2011)
"A fresh look at the ever-changing world of mutual funds Like all investment instruments, mutual funds continue to evolve. In the last decade however, there has been plenty of change, including market capitalization, the introduction of new types of funds, and the expansion of the mutual fund model to include investments in commodities. Getting Started in Mutual Funds, Second Edition offers a completely updated look at this popular investment vehicle, including everything from Morningstar?s new matrix of evaluating a fund?s investment style to implementing mutual funds into long-term investment strategies in retirement plans. Throughout the book, author Alvin Hall also focuses on the basics, like how to read a prospectus, how to evaluate ongoing fees and expenses, and how to gauge a fund?s performance. Acquaints you with the various types of mutual funds and how they are structured Explains important mutual fund terms and concepts New chapters include information on exchange-traded funds and how they compare to mutual funds in terms of performance, risk and fees Reveals how to assess a fund manager?s investment style and its impact on your returns Gain a better understanding of mutual funds and maximize your investment returns with Getting Started in Mutual Funds, Second Edition."--Provided by publisher